Secure Data Storage and Retrieval Using Adaptive Integrity Protocol Model in Cloud Environment - Sujitha, S; Mohana, SJ (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is provide a dynamically scalable resources provisioned as a service over the webpage. The third-party, on-demand, self-service, pay-per-use, and seamlessly scalable computing resources and services offered by the cloud environment promise to reduce capital as well as operational expenditures for hardware and software. Various distinct architectures are introduced and discussed according to their security and privacy capabilities and prospects. It provides four distinct models in form of abstracted multi-cloud architectures. These developed multi cloud architectures allow to categorize the available schemes and to analyze them according to their security reimbursement. An assessment of the different methods replication of applications, partition of application system into tiers, partition of application logic into fragments and partition of application data into fragments is given in particular. In addition, enabling public audit ability for cloud storage is of critical importance so that users can resort to an Integrity third party auditor (ITPA) to check the integrity of outsourced data and be worry-free. This paper proposes a secure cloud storage system supporting Isolation-preserving public auditing. It further extends the result to enable the ITPA to perform audits for multiple cloud users simultaneously and efficiently.